Transcriptomics of ammonium nutrition in the conifer Pinus pinaster Aiton - Ortigosa Peña, Francisco; Lobato-Fernández, César; Valderrama-Martín, José Miguel; Ávila-Sáez, Concepción; Cánovas-Ramos, Francisco Miguel; Cañas-Pendón, Rafael Antonio (My University, 2019)
Nitrogen is an important element for all living beings because it is part of macromolecules as significant as nucleic acids or amino acids. For plants, it constitutes a limiting factor in their growth and development1 due to their low natural availability in soils thus limiting primary production in ecosystems2. Conifers are a group of gymnosperm plants that form large forest extensions of vegetation, being the main constituents of forests in boreal ecosystems3 where ammonium is the main source of inorganic nitrogen4. Due to the characteristics of the soils in which conifers usually grow, these plants have developed a high tolerance to the presence of ammonium, which may constitute their main source of inorganic nitrogen5. The maritime pine (Pinus pinaster Aiton) is a conifer that has a wide distribution in the western Mediterranean area and has been widely used in reforestation, soil stabilization tasks and industrially. In recent years, maritime pine has been the subject of multiple omic studies that have resulted in the acquisition of important tools and resources6,7. The present work is focused on the analysis of the ammonium uptake and management efficiency, and its relationship with the biomass accumulation in maritime pine. For this purpose, several experiments have been developed in which pine seedlings have undergone different levels of ammonium nutrition, both in the short and long term. As a result of short-term experiments, the characterization of transcriptomic response to the process of ammonium nutrition (uptake and assimilation) is being studied at mRNA, lncRNA and miRNA level in roots. In relation to long-term experiments, ten different provenances of maritime pine seedlings were treated with different ammonium levels and the biomass changes were measured. The results obtained suggest the existence a certain phenotypic plasticity grade for this conifer.
Keywords: Nitrógeno -- Metabolismo; Coníferas; Amonio; Nitrogen metabolism; Conifer; Ammonium